If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + 2x) + -1 = 17 (3 * 2 + 2x * 2) + -1 = 17 (6 + 4x) + -1 = 17 Reorder the terms: 6 + -1 + 4x = 17 Combine like terms: 6 + -1 = 5 5 + 4x = 17 Solving 5 + 4x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4x = 17 + -5 Combine like terms: 5 + -5 = 0 0 + 4x = 17 + -5 4x = 17 + -5 Combine like terms: 17 + -5 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| 5y-(8-y)=2[-4-(3+5y)-13] | | 3(b+2)=4b-10 | | 10+3[x+2]=31 | | -5x+6=3x-9 | | log(12x+2)=log(2x-1)+1 | | 16xy+x^2+64y^2=0 | | 4+1f=17 | | 4k-12-6k=2k-6+6k+2 | | ln(2-1)=0 | | 4k-12-6=2k-6+6k+2 | | x^3-4x^2+6x=0 | | 8-3d=12 | | 432=-16t^2+64t+512 | | 2x^5-3x^4-2x^3+7x^2-2x-6=0 | | c^2-16h^4=0 | | 6r+3-2t+4=5 | | cosh(x)*cos(x)=1 | | 90=60+t | | -3b+23=80 | | 90=60t | | 2(k-4)=5k+2 | | x-4x-3=0 | | 2(k-4)=5k-2 | | 17x+7x=14-36 | | -4x-1+6x+4= | | 8(r-5)(r+5)=0 | | -4x+2+7x+3= | | 9x+4x-8x=8+7 | | 2(x-3)=(2x+5) | | 6y+2(3+6.5y)=2.5+15.5y | | 3+1b=5 | | 11p-9+8p-7+14=12p+9p+4 |